Experts Reaction to EAT-Lancet’s Planetary Health Diet - Wismen, Bendula; Thilsted, Shakuntala (CGIAR System Organization, 2025)
Hear from food systems and nutrition experts on their perspectives of the EAT-Lancet’s Planetary Health Diet, and how it can be implemented in Southeast Asia.